2020
DOI: 10.1038/s41467-020-17215-3
|View full text |Cite
|
Sign up to set email alerts
|

Spiking neurons with spatiotemporal dynamics and gain modulation for monolithically integrated memristive neural networks

Abstract: As a key building block of biological cortex, neurons are powerful information processing units and can achieve highly complex nonlinear computations even in individual cells. Hardware implementation of artificial neurons with similar capability is of great significance for the construction of intelligent, neuromorphic systems. Here, we demonstrate an artificial neuron based on NbO x volatile memristor that not only realizes traditional all-or-nothing, threshold-driven spiking and spatiotemporal integration, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
190
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(194 citation statements)
references
References 50 publications
1
190
1
2
Order By: Relevance
“…Secondly, despite of a high memory density using 2D semiconductors, the technique of large‐area 2D semiconductors with uniform electronic properties is still unmatured, which limits the yield and lateral size of arrays. These issues we believe will be conquered as the development of artificial neurons [ 60 ] and engineering of 2D semiconductors.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, despite of a high memory density using 2D semiconductors, the technique of large‐area 2D semiconductors with uniform electronic properties is still unmatured, which limits the yield and lateral size of arrays. These issues we believe will be conquered as the development of artificial neurons [ 60 ] and engineering of 2D semiconductors.…”
Section: Discussionmentioning
confidence: 99%
“…Letting a = 10, b = 2, c = 1, β 1 = β 2 = 3, f 1 = 0.003 and f 2 = 0.001, then w 2 = g(t), w 1 can be replaced by 4g(t) 3 − 3g(t) based on Table 2. Next, the corresponding equilibrium points E 0 and E ± are substituted into (11), and the following characteristic equation can be obtained as,…”
Section: Local Bifurcation and Stability Analysis Of Equilibrium Pointmentioning
confidence: 99%
“…For example, researchers in [10] used several types of BOs to drive electrodynamical systems. Authors in [11] demonstrated a specific type of artificial neuron with threshold-driven spiking and built a neural network for pattern recognition. Furthermore, it can also be applied to the study of stability and control design of pulsed power supply systems according to similar oscillation characteristics [12].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] In order to circumvent the limitations of complementary metal-oxide-semiconductor (CMOS) circuit-based threshold logic, a few types of single devices that can provide threshold operation were suggested using a magnetic tunnel junction (MTJ) and metal-insulator transistor (MIT) material. [16,17] However, only three Boolean logic functions were accomplished. In addition, these devices require additional materials that may not be easily implemented for conventional CMOS fabrication.…”
Section: Introductionmentioning
confidence: 99%